De-adoption and exnovation in the use of carotid revascularization: retrospective cohort study - Bekelis, Kimon (BMJ, 2017)
Objective To determine physician characteristics associated with exnovation (scaling back on use) and de-adoption (abandoning use) of carotid revascularization. Design Retrospective longitudinal cohort study. Setting Medicare claims linked to the Doximity database provider registry, 2006-13. Participants 9158 physicians who performed carotid revascularization on Medicare patients between 2006 and 2013. Main outcome measures The primary outcomes were the number of carotid revascularization procedures for each physician per year at the end of the sample period, and the percentage change in the volume of carotid revascularization procedures. Results At baseline (2006-07), 9158 physicians performed carotid revascularization. By 2012-13 the use of revascularization in this cohort had declined by 37.7%, with two thirds attributable to scaling back (exnovation) rather than dropping the procedure entirely (de-adoption). Compared with physicians with fewer than 12 years of experience, those with more than 25 years of experience decreased use by an additional 23.0% (95% confidence interval −36.7% to −9.2%). The lowest rates of decline occurred in physicians specializing in vascular or thoracic surgery, for whom the procedures accounted for a large share of revenue. Physicians with high proportions of patients aged more than 80 years or with asymptomatic carotid stenosis were less likely to reduce their use of carotid revascularization. Conclusion Surgeons with more experience and the lowest share in carotid revascularization practice reduced their use of the procedure the most. These practice factors should be considered in quality improvement efforts when the evidence base evolves away from a specific treatment.